2013
DOI: 10.1080/03098265.2013.801070
|View full text |Cite
|
Sign up to set email alerts
|

Technofetishism and online education: globalizing geography through virtual worlds

Abstract: Online education is becoming an increasingly popular venture for postsecondary institutions. It is an often controversial undertaking with proponents lauding the possibilities of technological advancements to increase access to education, while critics question the value and form of pedagogy on offer. This paper examines the potential and problems of online learning with reference to global geographic education. Drawing on the emergent literature on technology and education, it examines issues of design, inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Geographers are increasingly engaging with online education as an object of study (WinklerPrins et al, 2007; Heyman, 2013; Olds, 2013; Bose, 2014; Davis Conover and Miller, 2014; Rye, 2014; Slinger-Friedman, et al 2015; Sparke, 2017), though not at a pace that matches the rapid rise of online programs in higher education. Given this mismatch, there exists a need for focused engagement with the potential for these programs to create productive spaces of emancipatory possibility, spaces that geographies-of-education scholars, in particular, must attend to.…”
Section: Developing a Critical Geography Of Online Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Geographers are increasingly engaging with online education as an object of study (WinklerPrins et al, 2007; Heyman, 2013; Olds, 2013; Bose, 2014; Davis Conover and Miller, 2014; Rye, 2014; Slinger-Friedman, et al 2015; Sparke, 2017), though not at a pace that matches the rapid rise of online programs in higher education. Given this mismatch, there exists a need for focused engagement with the potential for these programs to create productive spaces of emancipatory possibility, spaces that geographies-of-education scholars, in particular, must attend to.…”
Section: Developing a Critical Geography Of Online Educationmentioning
confidence: 99%
“…The emergence of online teaching and learning as an increasingly popular distance education experience has pushed higher education into a debate about what contemporary, relevant, and accessible instruction should be, how it should be delivered, and whom it should serve. While geography as a discipline has begun to engage this debate (see WinklerPrins et al, 2007; Heyman, 2013; Olds, 2013; Smith and Jeffrey, 2013; Bose, 2014; Rye, 2014; Kalafsky and Conner, 2015, Sparke, 2017), geographers have been more active in critiques of the neoliberalizing processes associated with 21st-century higher education (Mitchell, 1999, 2003; Roberts, 2000; Larner and Le Heron, 2005; Dowling, 2008; Thiem, 2009; Moore et al, 2015; Morrissey, 2015; UKCPWG et al, 2015). It is, perhaps, the tendency to conflate online education with the neoliberal project that pushes geographers away from this topic.…”
Section: Introductionmentioning
confidence: 99%
“…Other research has shown that self‐directed online learning can outperform traditional classroom learning, which, however, has also emphasized that self‐learning requires self‐discipline, and thus direct supervision from instructors can be helpful (Bączek et al, 2021; Peine et al, 2016). Other than the benefits of health and safety, online learning can be convenient, time‐saving, flexible, cost‐effective, self‐pacing, and environmentally friendly (Adedoyin & Soykan, 2020; Bączek et al, 2021; Bose, 2014; Dhawan, 2020; Nambiar, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It has been studied for decades and has been heralded as one of the brightest horizons for education (Bose, 2014;Breetzke, 2007;Clark & Wilson, 2017;Hodges et al, 2020). A related educational strategy-massive online open courses, which was first introduced in 2008-has also been implemented for more than a decade (Bellack, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…17 Recently, with the enormous popularity of "Massive Online Open Courses" (MOOCs) -an increasing focus of university administrators in prestigious universities across wealthier countries as efforts to "internationalize" curricula -concerns about the homogenizing effects of online learning are increasingly debated 18 , with some suggesting that "technofetishism" is "emblematic of the neoliberal turn in education." 19 Indeed, concerns about online distance learning programmes also echo growing debates about information and communication technology (ICT) for development more generally 20 calling for vigilance about technological optimism to meaningfully address power imbalances in understandings of development. Yet, there has been a relative dearth of critical case study analysis of online development studies programmes.…”
Section: Introductionmentioning
confidence: 99%